Можливості вдосконалення медичних заходів по безпеці автотранспорту в Україні - Гоженко, А.І.; Лісобей, В.О.; Пономаренко, А.М. (Актуальні проблеми транспортної медицини, 2009)
На основании анализа данных литературы и собственных исследований определен широкий спектр проблем, решение которых может создать условия снижения опасности автотранспорта и до рожного движения в Украине. К ним относятся организационные решения Минздрава Украины по усовершенствованию систем профессионального медицинско
го отбора кандидатов в водители и водителей автотранспорта, санитарно гигиенического контроля за всеми этапами проектирования, строительства, реконструкции и ремонта автотранспортных средств, своевременности и полноты медицинской помощи пострадавшим в ДТП, также подготовки медицинского персонала с учётом специфики работы на автомобильном транспорте, по мнению авторов, позволит приблизиться к международным стандартам. On the basis of the analysis of the data of literature and own researches they have determined a wide spectrum of problems the solution of which can lead to reduction
of traffic dangers in Ukraine. They include some organizational decisions of the Ministry of Public Health on professional medical examinations candidates for drivers
and drivers themselves, sanitary and hygienic supervision for all stages of design, construction and reconstruction transport means, rendering of timely and complete
medical aid to the victims of incidents and training of medical persons with taking into account the specificity of automobiles operation. They authors believe that the
measures mentioned will allow to come close to international standards.